2019
DOI: 10.2460/ajvr.80.11.995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of site of sample collection and prandial state on blood glucose concentrations measured with a portable blood glucose meter in healthy dogs

Abstract: OBJECTIVE To compare glucose concentrations in peripheral venous and capillary blood samples collected from dogs before and after consumption of a meal and measured with a veterinary-specific portable blood glucose meter (PBGM). ANIMALS 12 dogs (96 blood samples). PROCEDURES A veterinary-specific PBGM was used to measure blood glucose concentrations. Glucose concentrations in capillary blood samples obtained from the carpal pad, medial aspect of a pinna, and oral mucosa were compared with glucose concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…The results of our study are not in agreement with the findings of a previous study conducted by Guevera et al (2019) on 12 healthy dogs, intending to evaluate the impact of the prandial state and sampling site on blood glucose concentrations. The authors claimed that the blood glucose collecting area is a prominent factor in glucose measurement as values obtained from capillary sites of the pinna reflect a more accurate and closer value to blood glucose measurement from the venous site than blood samples obtained from oral mucosa or carpal pad ( Guevera et al , 2019 ). This latter study is the only one that shows significant differences with the sampling site.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of our study are not in agreement with the findings of a previous study conducted by Guevera et al (2019) on 12 healthy dogs, intending to evaluate the impact of the prandial state and sampling site on blood glucose concentrations. The authors claimed that the blood glucose collecting area is a prominent factor in glucose measurement as values obtained from capillary sites of the pinna reflect a more accurate and closer value to blood glucose measurement from the venous site than blood samples obtained from oral mucosa or carpal pad ( Guevera et al , 2019 ). This latter study is the only one that shows significant differences with the sampling site.…”
Section: Discussioncontrasting
confidence: 99%
“…There are conflicting data on the concordance of blood glucose measurements from different sampling sites using PBGMs. Few studies have evaluated the performance of the PBGMs in various locations of the body; however, no study compares dogs to the results obtained from the blood collected on carpal pads, MEV, saphenous and cephalic veins ( Borin et al , 2012 ; Guevera et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst venipuncture site was standardised in this study, prandial state was not. A previous study concluded that prandial state had no significant effect on measured blood glucose concentration results using the AlphaTrak2 device (Guevara et al 2019), but no such studies have been performed using the AccuTell device. The current study did not determine whether prandial state may have affected the measured blood glucose concentration using the AccuTell device.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies evaluating the accuracy of humancalibrated portable glucometres when used in animals (Cohn et al 2000, Wess & Reusch 2000, Cohen et al 2009, Johnson et al 2009, Brito-Casillas et al 2014, Kang et al 2016, Mori et al 2016), but whilst the number of brands of commercially available veterinary-calibrated PBGM is increasing, a paucity of information exists with regards to their accuracy (Cohen et al 2009, Johnson et al 2009, Paul et al 2011, Kang et al 2016, Mori et al 2017, Guevara et al 2019. The accuracy of one of the most well-known veterinary PBGM, the AlphaTrak, has previously been investigated (Cohen et al 2009, Paul et al 2011, Kang et al 2016), but to date, no studies have investigated the accuracy of the AccuTell PBGM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation